1990
DOI: 10.1101/gad.4.5.740
|View full text |Cite
|
Sign up to set email alerts
|

Two genes differentially regulated in the cell cycle and by DNA-damaging agents encode alternative regulatory subunits of ribonucleotide reductase.

Abstract: Ribonucleotide reductase activity is essential for progression through the cell cycle, catalyzing the rate-limiting step for the production of deoxyribonucleotides needed for DNA synthesis. The enzymatic activity of the enzyme fluctuates in the cell cycle with an activity maximum in S phase. We have identified and characterized two Saccharomyces cerevisiae genes encoding the regulatory subnnit of ribonucleotide reductase, RNR1 and RNR3. They share -80% amino acid identity with each other and 60% with the mamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
236
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 284 publications
(255 citation statements)
references
References 41 publications
19
236
0
Order By: Relevance
“…This organism possesses no deoxynucleoside kinase activities, and thus, dNTP synthesis is entirely dependent on RNR (72). In S. cerevisiae, the levels of the subunits are controlled transcriptionally and the level of mRNA of the α subunit is increased during the S-phase of the cell cycle during normal growth, while the levels of mRNA for the β and β′ subunits remain largely unchanged (22,25,27,31). We have recently shown that the mRNA levels are correlated with the protein levels (D. L. Perlstein, M. Huang, and J. Stubbe, unpublished results).…”
Section: Discussionmentioning
confidence: 94%
“…This organism possesses no deoxynucleoside kinase activities, and thus, dNTP synthesis is entirely dependent on RNR (72). In S. cerevisiae, the levels of the subunits are controlled transcriptionally and the level of mRNA of the α subunit is increased during the S-phase of the cell cycle during normal growth, while the levels of mRNA for the β and β′ subunits remain largely unchanged (22,25,27,31). We have recently shown that the mRNA levels are correlated with the protein levels (D. L. Perlstein, M. Huang, and J. Stubbe, unpublished results).…”
Section: Discussionmentioning
confidence: 94%
“…6B). Because rad9 mutants show normal signaling for HU-induced RNR3 expression and are not themselves sensitive to HU (Elledge and Davis 1990), it was anticipated that rad9 mutants would have no effect on HUsensitivity of po12 mutants. Surprisingly, rad9 has a pronounced effect indicating that RAD9 may have a minor role in the response to HU arrest during S phase that is not detectable until the major pathway is knocked out.…”
Section: Transcriptional Response Of Other Checkpoint Mutants Shows Rmentioning
confidence: 99%
“…Yeast ribonucleotide reductase, a multi-protein complex, catalyzes one step in the dNTP production pathway. It is activated both as a normal part of the cell cycle and also in response to DNA damage [21,22,23,24,25]. RNR1 mRNA levels vary considerably with the cell cycle; the peak level occurs in the G1 phase [26].…”
Section: Introductionmentioning
confidence: 99%